2016
DOI: 10.1016/j.parkreldis.2015.09.027
|View full text |Cite
|
Sign up to set email alerts
|

Non motor subtypes and Parkinson's disease

Abstract: Word count abstract: 163 Word count manuscript: 2839 References: 30 2 AbstractNon motor symptoms (NMS) represent a significant burden in Parkinson's disease (PD) with numerous studies highlighting the importance of NMS both in "pre-motor" phase of PD as well as throughout the disease course. In part this has led the international Parkinson and Movement Disorder Society (IPMDS) task force to attempt a re-definition of PD incorporating NMS and not base the diagnosis solely on motor symptoms. While motor subtypes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
212
1
12

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 295 publications
(270 citation statements)
references
References 33 publications
26
212
1
12
Order By: Relevance
“…Indeed, there have been significant advances in understanding the pathophysiology of PD over the past decades and it is now better understood that the disease follows a defined clinical pattern, with a range of NMS defining the pre-motor phase [8]. In the prodromal stage, the most common NMS manifestations are olfactory impairment and raid eye movement behavior disorder while other features such as constipation, somnolence, apathy, fatigue may also be present [9].…”
Section: Animal Models Of Disease Pathologymentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, there have been significant advances in understanding the pathophysiology of PD over the past decades and it is now better understood that the disease follows a defined clinical pattern, with a range of NMS defining the pre-motor phase [8]. In the prodromal stage, the most common NMS manifestations are olfactory impairment and raid eye movement behavior disorder while other features such as constipation, somnolence, apathy, fatigue may also be present [9].…”
Section: Animal Models Of Disease Pathologymentioning
confidence: 99%
“…In one recent proposal, Sauerbier et al suggested at least seven distinct NMS dominant subtypes of PD: Cognitive dominant, apathy dominant, depression/anxiety dominant, sleep dominant, pain dominant, fatigue dominant and autonomic dominant [8]. Within this scheme, sleep-dominant and autonomic-dominant subtypes are grouped into a 'brainstem phenotype,' where the underlying pathology is thought to involve the brainstem and olfactory route.…”
Section: Understanding Pd Phenotype and Disease Progressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overlapping between groups was seen in many objective features of gait and balance. Several independent observers have reported (in early and untreated PD subjects) specific "clusters of non-motor symptoms dominant phenotype of PD" [26]. Patients with the PIGD subtype (predominantly characterized by axial motor involvement and increased cognitive impairment) are predisposed to falls, contrasting with the TD subjects [27].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with the PIGD subtype (predominantly characterized by axial motor involvement and increased cognitive impairment) are predisposed to falls, contrasting with the TD subjects [27]. These clinical particularities raised the supposition of different neuropathology, genetic and etiologic influences, distinct neurotransmitter systems, and functional imaging aspects [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%